Variable extent of clopidogrel responsiveness in patients after coronary stenting - Grossmann, Ralf; Sokolova, Olga; Schnurr, Axel; Bonz, Andreas; Porsche, Christian; Obergfell, Achim; Lengenfelder, Björn; Walter, Ulrich; Eigenthaler, Martin (Thrombosis and haemostasis, 2004)
Clopidogrel is an effective and specific inhibitor of ADP-induced platelet aggregation. After metabolic activation, the active clopidogrel metabolite irreversibly impairs the human platelet P2Y12 ADP receptor. Gialpha-protein activation and inhibition of vasodilator-stimulated phosphoprotein (VASP) phosphorylation are two key elements of the P2Y12 receptor pathway suitable for quantitation of clopidogrel effects. So far, only limited data exist about a diminished responsiveness to clopidogrel and underlying possible mechanisms. We investigated clopidogrel effects in 57 patients after percutaneous coronary intervention and stent implantation by flow cytometry for the analysis of intracellular VASP phosphorylation. Patients were treated with a 300 mg clopidogrel loading dose, followed by 75 mg/day clopidogrel in combination with 100 mg/day aspirin. Samples were drawn after a median of 5 days of clopidogrel treatment. Considerable differences in the responsiveness to clopidogrel could be observed and it was shown that 17.5% (10/57) of the patients revealed an inadequate responsiveness to clopidogrel despite continuation of clopidogrel intake. Comparable amounts of Gialpha and VASP were found in two clopidogrel low-responding patients as well as in two responding patients. To exclude a molecular defect of P2Y12 ADP receptor, the P2Y12 receptor gene of eight clopidogrel treated patients (seven patients with inadequate responsiveness, one responder) was sequenced. We only found a single silent mutation in exon 2 at position 1828 (GA). We suggest that individual differences in clopidogrel metabolization could cause relevant variations in clopidogrel responsiveness despite the use of a 300 mg clopidogrel loading dose.